Acute retinal necrosis – a case report - Oleksy, Piotr; Karska-Basta, Izabella; Kubicka-Trząska, Agnieszka; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
We present a case of acute retinal necrosis (ARN) which is a rare but devastating and rapidly progressive viral retinitis. It is caused mainly by Herpes simplex virus (HSV) or Varicella zoster virus (VZV) (2), but also Cytomegalovirus (CMV) and Epstein-Barr virus infections may be aethiological factors of ARN. A 17 years old male patient was referred with history of painful sudden worsening of visual acuity in the left eye and the presence of floaters in the visual field of the right eye. Based on the ophthalmological examination the diagnosis of bilateral ARN was established. Aqueous humor aspirates were analyzed using polymerase chain reaction (PCR) for Herpes simplex virus (HSV), Varicella zoster virus (VZV), Cytomegalovirus (CMV) and Epstein-Baar virus (EBV). PCR confirmed the presence of Varicella zoster virus in aqueous humor samples. Prompt systemic antiviral therapy combined with steroids was initiated. Since a rapid and accurate diagnosis is crucial for prompt administration of antiviral therapy, PCR-based analysis of intraocular fluids provides a valuable tool in the establishing an etiologic factor in patients with retinitis caused by herpesvirus.